Knowledge, attitude and practice of hospital staff regarding the solid waste management in Hayatabad Medical Complex Peshawar - Shah, Inayat (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Background Health care waste management is a serious public health concern and poses a variety of health and safety hazards for patients and health care workers. This study was conducted to assess the knowledge, attitude and practices of hospital staff regarding the solid waste management in Hayatabad Medical Complex Peshawar. Material & Method In this cross sectional study, through simple random sampling technique a total of 257 (n=257) hospital staff were interviewed based on knowledge, attitude and practices regarding hospital waste management through a questionnaire. Results Majority of the staff members (80.16%) were in age ranges 20-40 years with mean age of 35 years with SD ± 1.26; with male preponderance (54.86%). 29.18% staff members had good knowledge; 40.08% staff members had average knowledge, and 30.74% staff members had poor knowledge. Furthermore, 70.04% staff members had positive attitude and 61.8% staff members were practicing proper waste management. Conclusion The hospital staff reported a low level of knowledge about the hospital waste mangaent, however, attitude and waste management practice of the concerned staff was up to the standards but needed further improvement. Thus frequent staff awareness campaigns and trainings may be conducted to improve the knowledge and to change the behavioral practices of the health staff regarding adequate management and disposal of bio medical waste.